Incidence, risk factors and results of treatment of rhegmatogenous retinal detachment after 23 gauge vitrectomy in proliferative diabetic retinopathy - Kerimov, M. I.; Kasimov, E. M.; Aliyeva, I. J. (Ukrainian Journal of Ophthalmology, 2026)
Purpose. To study the incidence, risk factors, and results of treatment of retinal detachment developed after 23 gauge vitrectomy in patients with proliferative diabetic retinopathy. Material and Methods. A total of 416 patients (481 eyes) were operated on for the sequelae of proliferative diabetic retinopathy at Department of Ocular Complications of Diabetes Mellitus in National Centre of Ophthalmology named after acad. Zarifa Aliyeva within the period from July, 2009 to December, 2015. 23 gauge pars plana vitrectomy was performed in all patients using an Accurus 800 CS surgical system. The post-operative follow-up period of the patients after vitrectomy was 20.7±17.8 months with 1 month and 96 months as min and max, respectively. Results. With one surgery, complete retinal attachment was noted in 459/481 eyes (95.4%); 21/481 eyes (4.4%) had rhegmatogenous retinal detachment in the early post-operative period (within one month). In other four eyes, retinal detachment developed after silicone oil removal and, in other three eyes, in a remote post-operative period (within 3-24 months). There were a total of 28 cases of rhegmatogenous retinal detachment. Logistic regression analysis revealed that complete adhesion of the posterior hyloid membrane (more than two quadrants in the periphery), tractional-rhegmatogenous detachment and tractional detachment as vitrectomy indications, expressed bleeding during the membrane dissection, and the presence of intraoperative iatrogenic breaks increased the risk of postoperative retinal detachment development. Re-operations were performed in 24/28 eyes and anatomical success was achieved in 20/28 eyes (71.4% of all eyes with retinal detachment). Comparing to baseline, visual acuity increased in 13/28 eyes (46.4%), unchanged in 4/28 eyes (14.3%), and decreased in 11/28 eyes (39.3%). Conclusion. Rhegmatogenous retinal detachment developed after DR vitrectomy is still an extremely unfavorable complication and is characterized by quick development of ischemic and proliferative changes in the retina. Its timely detection and surgical intervention can partially preserve the visual functions in some cases.